Data-base: harga bahan dan buruh binaan - Khalid, Abd. Ghani; Abdul Hamid, Razali; Mohd. Yusof, Zakaria; Misnan, Mohd. Saidin (Faculty of Built Engineering, 2006)
Labour are the most important cost element in a construction project. However, the labor prices are not fixed in market. There are variation of price that can be offered by the contractor and sub-contractor. The price are different based on factors such as skill, types of project, location of project, demand and supply of labour, level of life, citizen, gender and races. For that reason, this study was carrying out to identify and compare the labour price in range and average aspect according to location and tred and also the factors which are influence it. The study scope only focuses in Terengganu, Johor and Kuala Lumpur. Research methodology that has been used for this study is questionnaire forms. The respondents are contractor and sub-contractor. From the findings, Kuala Lumpur is the location which offered the highest labour price which is RM90.00 compare with Terengganu and Johor. The treds which offered with high price by the all location are carpenter and joiner, plant operator, fitter, pneumatic tool operator, blasting operator and piling rigger. The result from analysis shown that the most influence factors for the variation of labour price are skill and location of project. While, races is the one factor which is almost not influence the variation of labour price.